Investigation on the propagation characteristics of pressure wave during managed pressure drilling - Hou, Yanan; Li, Zhong; Yin, Zhiming; Fan, Baitao; Ma, Yingwen; Yang, Xiangqian; Tian, Deqiang; Cai, Wenjun; Ren, Meipeng; Zhang, Xingquan (Frontiers in Energy Research, 2024)
The small difference between formation pressure and fracture pressure in offshore oil and gas reservoirs poses a huge challenge to drilling. Managed pressure drilling (MPD) technology, as a drilling technique that can accurately control bottomhole pressure, is an effective technique to solve this challenge. In MPD technology, the pressure wave propagation behavior and mechanism in the wellbore induced by wellhead backpressure are crucial for parameter design and efficient application. In this paper, pressure wave propagation characteristics and mechanism in gas-liquid flow were investigated with a new proposed pressure wave velocity model that considers inter-phase mass transfer effect. This new model and its solution algorithm were verified with experimental data in literature. The influence of gas invasion stage, drilling fluid type, drilling fluid density and backpressure on pressure wave propagation characteristics were investigated. Results show that the time for pressure wave induced by wellhead backpressure in the wellbore cannot be ignored in the design of the backpressure value during MPD. This propagation time increases with occurrence of gas invasion. Moreover, the propagation time in water-based drilling fluid is longer than that in oil-based drilling fluid, which is because the interphase mass transfer between invaded gas and oil-based drilling fluid. The influence mechanism of high drilling fluid density and wellhead backpressure on pressure wave propagation characteristics is due to the suppression of gas invasion process. These findings could be used as guides in parameters design and optimization in MPD.